Reconstruction of Husband-Wife Sexual Relations in Shafi'i Jurisprudence from the Perspective ff Maqāṣid Al-Usrah and Maṣlaḥah and its Relevance to Article 8 of Law No. 23 of 2004 on the Elimination of Domestic Violence - Muhammad Ali Mutharom; Ahmad Muslimin; Habib Sulthon Asnawi (Assyfa Journal of Islamic Studies, 2026)
This study examines the reconstruction of husband-wife sexual relations in Shafi'i jurisprudence from the perspectives of maqāṣid al-usrah (family objectives) and maslahah (public interest), and analyzes its relevance to Article 8 of Law No. 23 of 2004 on the Elimination of Domestic Violence. Shafi'i jurisprudence constructs the legitimacy of sexual relations upon the marriage contract (akad), which gives rise to the right of istimtā' and the obligation of tamkīn, bounded by the principles of mu'āsharah bi al-ma'rūf, the prohibition of ḍarar, and recognition of legitimate 'udzur. Through the lens of maqāṣid al-usrah and maslahah, this study finds that the fundamental objectives of marriage are to realize sakinah, mawaddah, rahmah, as well as the protection of life, honor, and lineage. Article 8 of the Domestic Violence Law, which prohibits coercive sexual relations within the household, has substantive relevance to maqāṣid al-usrah as it aims to protect wives from ḍarar that damages family maslahah. However, there is a conceptual tension at the epistemological level: Shafi'i jurisprudence departs from akad and relational obligations, while positive law departs from consent and individual protection. This doctrinal legal research recommends a reconstruction of sexual relations based on maqāṣid al-usrah that clearly distinguishes between destructive sexual violence and relational conflicts in fulfilling obligations, and offers a proportional and contextual layered protection model.